Speech intelligibility improvement based on adaptive exponential smoothing factor - Janardhanarao, S; Krishna chaitanya, J; A David, B (International Journal of Engineering and Technology, 2018)
This paper aims to increase the intelligibility of the speech content in the noisy speech signal. The approach presented in this paper tries to improve the intelligibility by adaptively re distributing the speech energy with exponential smoothing factor. Experiments were conducted on the different types of noises in noisy signal and found that there is a significant increase in intelligibility while preserving the quality of it.